Endpoint Security in Remote Work Environments: Addressing the unique challenges of securing endpoints in remote work scenarios - Sri Kanth Mandru (North American Journal of Engineering Research, 2023)
The change to remote work, furthered by the COVID-19 pandemic, has caused core office environments to become distributed networks of home offices and other remote settings that are not easy to protect from cyber threats. This paper aims to discuss the specifics of endpoint protection – laptops, mobiles, tablets, and other devices connected to the corporate network and used in remote work. Some challenges include new attack vectors, different and uncontrolled endpoints, insecure networks, the absence of physical security for the devices, and increased phishing and social engineering attacks. To these, we have the following remedies: the endpoint protection measures such as antivirus, EDR, and VPNs. Other security measures like the MFA and the zero-trust security model build on the security layer by allowing only authorized users to access corporate resources. A proper approach to managing devices and delivering frequent updates ensures endpoint protection while raising awareness and training to keep users vigilant about threats. Therefore, by taking the abovementioned measures, organizations can reduce risks, enhance compliance with the legislation on personal data protection, and address various occurrences. The following are some possible benefits of implementing these solutions: better security, increased employee efficiency, and fewer charges resulting from security incidents. This paper also examines the appropriateness of these strategies for organizations of different sizes and across industries. It considers other future advancements of endpoint protection, such as AI and enhanced Zero Trust for conducting business securely outside the office.